Establishment of the Scheme of Mutual Location of Corpses in Police (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article is based on the scheme of mutual arrangement of housings for the formation of the initial irrigation ditch when preparing the soil for planting rice crops. It was determined that the arrangement of the right and left-turning bodies in a lister in a pair-symmetrical position is the most optimal scheme for plowing the area of planting crops.